2008
DOI: 10.1002/mrm.21636
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of liver viscoelasticity using multifrequency MR elastography

Abstract: MR elastography (MRE) allows the noninvasive assessment of the viscoelastic properties of human organs based on the organ response to oscillatory shear stress. Shear waves of a given frequency are mechanically introduced and the propagation is imaged by applying motion-sensitive gradients. An experiment was set up that introduces multifrequency shear waves combined with broadband motion sensitization to extend the dynamic range of MRE from one given frequency to, in this study, four different frequencies. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
193
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 22 publications
8
193
2
Order By: Relevance
“…This multidimensional information was combined into two maps of viscoelastic parameters which are related to the elasticity and viscosity of the tissue. Our previous studies using MMRE in the liver [23,34,35] have shown that the liver is a highly viscous organ giving rise to signif- icant dispersion of the shear modulus values within the applied range of drive frequencies (25 Hz to 62.5 Hz). Notably, MDEV-inversion used here sacrifices the dispersion-related information in order to stabilize the inversion and improve the certainty and precision of elastograms (i. e. |G * |-and φ-maps).…”
mentioning
confidence: 99%
“…This multidimensional information was combined into two maps of viscoelastic parameters which are related to the elasticity and viscosity of the tissue. Our previous studies using MMRE in the liver [23,34,35] have shown that the liver is a highly viscous organ giving rise to signif- icant dispersion of the shear modulus values within the applied range of drive frequencies (25 Hz to 62.5 Hz). Notably, MDEV-inversion used here sacrifices the dispersion-related information in order to stabilize the inversion and improve the certainty and precision of elastograms (i. e. |G * |-and φ-maps).…”
mentioning
confidence: 99%
“…Thus, we will estimate the experimental specificities of SE-MRE and DENSE-MRE as ␦⌽ SM ϭ r SM ⅐ ⌽ SM (Eqs. [15,16]) and ␦⌽ DM ϭ r DM ⅐ ⌽ SM (Eqs. [12,15]).…”
Section: Spectral Properties Estimation (Experiments and Estimation)mentioning
confidence: 99%
“…[15,16]) and ␦⌽ DM ϭ r DM ⅐ ⌽ SM (Eqs. [12,15]). DENSE-MRE, SE-MRE and FEHM spectral properties (sensitivity, specificity) are calculated using Eqs.…”
Section: Spectral Properties Estimation (Experiments and Estimation)mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic Resonance Elastography (MRE) can directly visualise and measure tissue elasticity [5][6][7][8], and has been applied to resolve stiffness characteristics of a variety human tissues and organs, such as muscle [9][10][11][12], breast [13][14][15][16][17], liver [18][19][20] and the brain [21][22][23][24][25][26][27][28][29]. MRE acquisition requires application of mechanical waves to tissue within the MRI, phase-contrast MR pulse sequence extended with motion encoding gradient (MEGs), and sophisticated inverse problem methods to identify an elastic modulus map of the tissue.…”
Section: Introductionmentioning
confidence: 99%